Medea and others plays - Euripides (London : Penguin Books, 1963)
The Catholic University of America Speech and Drama Department, Rev. Gilbert V. Hartke, O.P., head, presents "Medea," by Euripides, directed by James D. Waring, adapted by Leo Brady, choral interpretation by Josephine McGarry Callan, settings and lighting by James D. Waring, costumes designed by Joseph F. Bella.
University Theatre, February 1-16, 1963.
Title devised by Library staff.
Cast: Carol Churas, Marilyn Morton, John Miller, Frederic De Santis, John Starrs, Marian McDonnell, William Hicks, Chet Carlin, James Way, Richard Kearney, Randy Jones, Dennis McGovern, Robert Ingel and Paul Brooks or Jerry Renzi and Ralph Bonuccelli, Dana Haskell, Sylvia Pegis, Ann Marie Shea, Dolores Miner, Mahalla Lenzi, Karen Lachowitch, Beatrice O'Donnell, Iva Jean Doutt, Mary Ellen Kelley, Doris Bucher, Fay Anne Mazzanti, Elizabeth Lenehan.
LC copy has notations by Coe.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: Theater programs -- Washington (D.C.); Theater programs -- 1963.